Drama Boxiana: Spectacle and Theatricality in Pierce Egan’s Pugilistic Writing - Snowdon, David (Romanticism on the Net, 2007)
AbstractIn the evolving literary sub-genre of sports writing, Pierce Egan (c. 1772-1849) infused his prizefight commentaries with a theatricality that extended their appeal beyond the confines of a diverse sporting set (‘the Fancy’). This paper examines prominent factors that rendered Egan’s approach distinctive, and how it functioned as a means of invigorating the sporting narrative. A major feature is Egan’s blend of inventive imagery and linguistic exuberance, which constituted an integral part of his animated pugilistic writing, primarily in the Boxiana series (1812-29), and this could be identified as the ‘Boxiana style’.Questions arise concerning the possibly limited accessibility of the ‘flash’ argot to more refined readers, and whether Egan’s classical and chivalric allusions are undercut by their collocation with pantomimic touches. Similarly, did the more cultivated references risk alienating those whose appreciation was limited to a mixture of the slang, slapstick, and gambling elements? My paper discusses how Egan’s Boxiana style transcended differing attitudes prevalent within a socially diverse readership that mirrored the fusion of Regency types attending pugilistic contests. Egan’s commentaries accentuated the spectacle of a sporting event, and promoted a visualisation process that eroded social barriers as a stage production might appeal to a heterogeneous theatre audience. The performance aspect, that played such a pivotal role in Egan’s pugilistic reporting, is a dominant theme in this discussion.